Pharmacokinetic Study of Oral 14C-Radiolabeled Hyzetimibe, A New Cholesterol Absorption Inhibitor - Liao, Jianwei; Wang, Xin; Li, Zhenyu; Ouyang, Dongsheng (Frontiers in Pharmacology, 2021)
Background and objectives: Hyzetimibe is a candidate drug as the second-in-class cholesterol absorption inhibitor and lowers plasma levels of LDL-C by blocking the Niemann-Pick C1-like 1 protein, a transporter mainly expressed in the intestine to allow dietary cholesterol to enter body from the intestinal lumen. The previous studies on drug metabolism in healthy volunteers were not enough to show the bio-transformation and excretion pathway, especially Hyzetimibe could maintain pharmacological action for a long time through hepatic-intestinal circulation. Further more, it was not clear whether the little difference of chemical structure between Eztimibe and Hyzetimie would result in different pharmacokinetic characteristics. Given that drug molecular targets was in the intestine and the significant hepatic-intestinal circulation metabolic characteristic, the study of oral 14C radiolabeled drug would play a more important role than routinely metabolic drugs. Methods: Following an overnight fast before medication, 6 healthy male volunteers swallowed the investigational product suspension containing 20 mg/about 100 μCi of 14C-Hyzetimibe as a single dose and whole blood, plasma, urine, and feces were collected and measured. Pharmacokinetic variables of Hyzetimibe and its metabolites were calculated and statistically analyzed according to obtained concentration data. Safety data was collected throughout the study. Results: The major metabolite detected in plasma was Hyzetimibe-glucuronide which accounted for 97.2% of total plasma radioactivity. The mean cumulative excretion of total radioactivity of dose was 16.39% in urine and 76.90% in feces. Unchanged drug in feces and Hyzetimibe-glucuronide in urine was identified as the major component respectively. The main metabolic conversions of Hyzetimibe were glucuronidation (M1), mono-oxidation (M4), mono-oxidation with further sulfonation (M7). Hyzetimibe was considered generally safe and well-tolerated. Conclusion: The study of 14C radiolabeled Hyzetimibe provided a full profile of the bio-transformation and excretion routes of Hyzetimibe for deeply understanding the characteristics of Hyzetimibe. The change of hydroxyl group in the structure made Hyzetimibe easier to combine with glucuronic acid and led to more excretion than Ezetimibe in urine, which highlighted the necessity to further investigate the difference of pharmacokinetic impact on efficacy and safety between Hyzetimibe and Ezetimibe.